THE INFLUENCE OF THE TYPE AND CONCENTRATION OF LEAF FERTILIZIER ON THE GROWTH AND PRODUCTION OF BEAN PLANTS (Phaseolus vulgaris L.) - Afifuddien Anwary; Pramono Hadi, Srie Juli Rachmawatie (PROSIDING, 2022)
This research studies to study various kinds and concentrations of fertilizer on the growth and yield of green beans. This research was carried out in February to April 2019, in Sawah Village, Palur, Kec. Mojolaban, Sukoharjo Regency, Central Java. This study used a factorial method with the basic pattern of a Completely Randomized Design (CRD) consisting of two regulatory factors with three replications. The first administration factor, namely the type of leaf fertilizer (P) consisting of 3 types (P1 = Bayfolan leaf fertilizer, P2 = Nasa leaf fertilizer, and P3 Atonic leaf fertilizer). The second concentration factor, leaf fertilizer concentration (D) which consists of three kinds (D1 = concentration of leaf fertilizer 2 cc / L air, D2 = leaf fertilizer concentration 3 cc / L air, D3 = leaf fertilizer concentration 4 cc / L air). The results showed that the best leaf fertilizer was Atonic leaf fertilizer because the results obtained from the number of pods, fruit length, fruit weight, fresh stover weight and dry stover weight were higher for Bayfolan and NASA leaf fertilizers. The best treatment of leaf fertilizer concentration is Atonik leaf fertilizer which is 4 cc / L air which is indicated by the number of pods, fruit length, fruit weight and dry stover weight parameters. Nuts, heavy fruit, fresh stover fruit and dry heavy stover fruit. The combination of P3D3 concentration (Atonic leaf fertilizer at a concentration of 4 cc / L air) gave the best results on the parameters of the number of pods (18 pieces) and fruit length per plant (24cm). The combination of P2D2 (Nasa leaf fertilizer at a concentration of 3 cc / L air) gives the best results on the fresh fruit weight parameter that is 85.97 g. The combination of P2D3 administration (Nasa leaf fertilizer at a concentration of 4cc / L water) gives the best results at a fresh stover weight of 117.00g. , and the combination of P3D1 (Atonic leaf fertilizer at a concentration of 2 cc / L air) gave the best results at dry stover weight, 57.93. Keywords: leaf fertilizer, beans, fertilizer concentration, plants, production.